The Influence of Transformational and Transactional Leadership on Followers' Acceptance to Change. The Comparative Analysis of A Banking and Information Technology Organisation - Wong, Wei Yeng (2016)
In recent times, organisations worldwide face increasingly hostile environments that stem from the various forces within and out of the organisation. The challenging situations are imposed upon them due to the unceasing forces of globalisation, competition, changing technology and customers' demand. As such, organisational change becomes a regularity, particularly in organisations that operate on a large and complex scale. Change is also an imperative for the sustenance and maintenance of both financial and operational performance of organisations. The success of organisational change, nonetheless, is critical as failure rates were reported to be close to 70%. Such high rates of failure cause organisational change a worrying situation for leaders who embark on change initiative. On the other hand, leaders are not only individuals who influence change. Not only that the followers are chief receiver of change but they play considerable roles on organisational change and impact its outcomes. For this reason, positive behavioral responses from the followers, specifically the levels of acceptance to change, are pivotal for successful initiation as well as the long term positive outcomes of the change. Extant literature of leadership theories have signified transformational and transactional leadership as the two most eminent leadership styles of contemporary organisations. Transformational leadership concerns leaders who are capable of transforming their followers with positive values and commitment to shared goals through influential motivation while transactional leadership focuses on the social exchange process through goal settings and providence of rewards when follower perform in accordance to their expectations. This study deployed the Multifactor Leadership Questionnaires (MLQ) survey instrument and semi-structured interviews to achieve the objective of making comparative analysis on the effects of the transformational and transactional leadership styles towards followers' acceptance to change behaviour. This study disposed two organisations operating in Kuala Lumpur as the target population; Organisation A, a publicly-listed banking organisation and Organisation B, an IT services and products manufacturer. The two organisations were chosen due to their adequate size and they were undergoing changes in terms of organisational restructuring at the time of data collection. 174 participantsout of 250 completed the quantitative survey from both organisations, giving a 69.6% response rate. The results of this study, from both quantitative and qualitative perspective, supported the findings from literature that transformational leaders, in general, are capable of increasing the levels of acceptance to change greater than transactional leaders. In terms of theoretical contributions, this study has presented a consolidated conceptual framework model that identifies the transformational and transactional leadership and measure followers' acceptance to change. In accordance to the theoretical and practical implications described in this study, five recommendations that converged on principles that promote transformational leadership were expounded for Organisation A and Organisation B. Certain aspect of transactional leadership, such as contingent reward, was also advocated alongside transformational leadership in order to expand the followers' acceptance to change for both organisations.